PTU-033 Endoscopic Mucosal Resection of Adenomas and Sessile Serrated Polyps, is there a Difference in Complication Rates?. (17th August 2016) - Kassam, R; Subhani, J
Abstract : Introduction: Introduction: within a regional, DGH based, EMR service, we evaluated whether there is a difference in the complication rate of EMR of adenomas and SSA/P's. Methods: Method: from January 2007 to February 2016 we prospectively collected data for a single endoscopist (a consultant gastroenterologist, within our institution), for EMR of all large (>19mm) non-pedunculated polyps. A standard EMR technique was used in all patients, a lifting solution consisting of colloid, methylene blue and adrenaline was injected into the submucosal plane. Appropriately lifting lesions were removed with the use of diathermy through a range of standard snare's. A CONMED diathermy unit using Endocut setting was used for all EMR's. Lesions were removed either en bloc or piecemeal dependent upon the safety of either resection technique. Following snare resection any residual polyp tissue was treated with APC. Following uncomplicated EMR's patients were discharged home with two follow up telephone interviews with a sister in the endoscopy unit scheduled for day 1 and 14 post procedure assessing for complications. Adverse events recorded included perforation, late bleeding or admission. A "site check" was routinely performed at 3 months and if clear at 12 months following the EMR, to assess for recurrence. Histological analysis was carried out by a GI pathologist at our hospital, sessile serrated lesions were classified as per the WHO (2010) classification: 1 SSA/P's without cytological dysplasia, SSA/P's with cytological dysplasia, traditional serrated adenomas and hyperplastic polyps. Results: A single endoscopist attempted 386 adenoma resections, completing 379 of these. 3 (0.8%) perforations were diagnosed. 20 (5.2%) late bleeds occurred in the adenoma group, 12 (3.1%) of patients with late bleeding required admission. Recurrence in the adenoma group was 10.9% at 12 months(249 patients have completed there 1 year follow up to date). During the same period the same endoscopist attempted the resection of 19 SSP's. In this group 3 (16.7%) perforations were diagnosed, there was the same number of patients with delayed bleeding but only 2 (11.1%) patients required admission for bleeding. Recurrence of SSP's at 12 months 0%(5 patients have completed their 1 year follow up colonoscopy to date). Conclusion: Though a clear difference in size of the cohorts, our data demonstrates a strikingly higher rate of perforations in the SSP group. We note no significant difference in complication rates was observed in a large prospective, multicentre study of 2000 lesions. 2 References: 1 Snover DC, et al . Serrated polyps of the colon and rectum. WHO Classification Tumours of Digestive System. 2010:160–165. 2 Pellise M, et al . EMR for large serrated lesions in comparison with adenomas: a prospective multicentre study of 2000 lesions. Gut online first, January 2016. Disclosure of Interest: None Declared